Biomimetic 3D tissue printing for soft tissue regeneration. (September 2015) - Pati, Falguni; Ha, Dong-Heon; Jang, Jinah; Han, Hyun Ho; Rhie, Jong-Won; Cho, Dong-Woo
Abstract: Engineered adipose tissue constructs that are capable of reconstructing soft tissue with adequate volume would be worthwhile in plastic and reconstructive surgery. Tissue printing offers the possibility of fabricating anatomically relevant tissue constructs by delivering suitable matrix materials and living cells. Here, we devise a biomimetic approach for printing adipose tissue constructs employing decellularized adipose tissue (DAT) matrix bioink encapsulating human adipose tissue-derived mesenchymal stem cells (hASCs). We designed and printed precisely-defined and flexible dome-shaped structures with engineered porosity using DAT bioink that facilitated high cell viability over 2 weeks and induced expression of standard adipogenic genes without any supplemented adipogenic factors. The printed DAT constructs expressed adipogenic genes more intensely than did non-printed DAT gel. To evaluate the efficacy of our printed tissue constructs for adipose tissue regeneration, we implanted them subcutaneously in mice. The constructs did not induce chronic inflammation or cytotoxicity postimplantation, but supported positive tissue infiltration, constructive tissue remodeling, and adipose tissue formation. This study demonstrates that direct printing of spatially on-demand customized tissue analogs is a promising approach to soft tissue regeneration.